Kontekstualisasi Penafsiran Ayat-Ayat Teror dalam Al-Quran - Syauqi, Muhammad Labib (MAGHZA: Jurnal Ilmu Al-Qur’an dan Tafsir, 2020)
The phenomenon of the emergence of the terrorist movement can not be separated from the existence of radical groups in understanding Islam, the question is, is it true that violence and terrorism that emerged, were found from the text of the Qur'an itself, or it turns out the verses of the Qur'an ' Is it interpreted to legitimize all acts of terrorism that they commit for power? Many studies related to terrorism from the social, political, and theological aspects, however, this research tries to approach it using Abdullah Saeed's Contextual Approach theory which has never been done before. Contextual Approach which is translated in the framework of the value hierarchy theory initiated by Abdullah Saeed tries to explore and uncover the content of values ​​that exist in each Al-Qur'an text and at the same time also reveal the maghza (significance) of the text an-sich then find the contextualization relevant way.